Changing minds : the art and science of changing our own and other people's minds - Gardner, Howard (Boston, Mass. : Harvard Business Review Press, 2006)
Minds are exceedingly hard to change. Ask any advertiser who has tried to convince consumers to switch brands, any CEO who has tried to change a company's culture, or any individual who has tried to heal a rift with a friend. So many aspects of life are oriented toward changing minds--yet this phenomenon is among the least understood of familiar human experiences. Now, eminent Harvard psychologist Howard Gardner, whose work has revolutionized our beliefs about intelligence, creativity, and leadership, offers an original framework for understanding exactly what happens during the course of changing a mind--and how to influence that process. Drawing on decades of cognitive research and compelling case studies--from famous business and political leaders to renowned intellectuals and artists to ordinary individuals--Gardner identifies seven powerful factors that impel or thwart significant shifts from one way of thinking to a dramatically new one. Whether we are attempting to change the mind of a nation or a corporation, our spouse's mind or our own, this book provides insights that can broaden our horizons and improve our lives.-- by Publisher's description
The contents of the mind -- The forms of the mind -- The power of early theories -- Leading a diverse population -- Leading an institution : how to deal with a uniform population -- The creative geniuses change minds indirectly through science, scholarly breakthroughs, and works of art -- Mind changing in a formal setting -- Mind changing up close -- Changing ones own mind -- Epilogue: The future of mind changing
Gifted by Professor Jamshed Bharucha
Includes bibliographical references and index
Keywords: Change (Psychology); Persuasion (Psychology; Influence (Psychology